REKONSTRUKSI DAN REPOSISI PENDIDIKAN ISLAM DALAM MERESPON TANTANGAN DUNIA PENDIDIKAN DI INDONESIA - Moch Kalam Mollah (NUR EL-ISLAM : Jurnal Pendidikan dan Sosial Keagamaan, 2016)
ne"> Globalization era is the reality that we ought to face it. Theongoing changes and some problems of education as the impactof globalization must be faced and solved as well as possibleboth on discourse and concrete or action policy phases.Inevitably, the islamic education will be involved and insistedto be able to give a significant contribution. This paper describesurgency of the islamic education to reconstruct its self before,both in the institutional management, programs and learningaspects, and we must realize that the religious education has theimportant role in national education system as “core ofeducation”. What must be reconstructed, why and how toreconstruct the islamic education? This paper answers thosequestions.Kata Kunci : Reposisi, Rekonstruksi dan Respon.